2005
DOI: 10.1051/0004-6361:20042446
|View full text |Cite
|
Sign up to set email alerts
|

The VLT-FLAMES survey of massive stars: Observations in the Galactic clusters NGC 3293, NGC 4755 and NGC 6611

Abstract: Abstract. We introduce a new survey of massive stars in the Galaxy and the Magellanic Clouds using the Fibre Large Array Multi-Element Spectrograph (FLAMES) instrument at the Very Large Telescope (VLT). Here we present observations of 269 Galactic stars with the FLAMES-Giraffe Spectrograph (R 25 000), in fields centered on the open clusters NGC 3293, NGC 4755 and NGC 6611. These data are supplemented by a further 50 targets observed with the Fibre-Fed Extended Range Optical Spectrograph (FEROS, R = 48 000). Fo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
163
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 164 publications
(171 citation statements)
references
References 84 publications
(165 reference statements)
8
163
0
Order By: Relevance
“…The spectral types derived from the BCD method agree very well with the determinations by Evans et al (2005) using the MK system, with the Hγ equivalent widths and the Balona & Crampton (1974) calibration, for 14 stars in common. The exception is CPD−59 4530, for which we determine a spectral type of B6 V in accordance with Feast (1963) …”
Section: Ngc 4755supporting
confidence: 73%
See 2 more Smart Citations
“…The spectral types derived from the BCD method agree very well with the determinations by Evans et al (2005) using the MK system, with the Hγ equivalent widths and the Balona & Crampton (1974) calibration, for 14 stars in common. The exception is CPD−59 4530, for which we determine a spectral type of B6 V in accordance with Feast (1963) …”
Section: Ngc 4755supporting
confidence: 73%
“…4.2.2, as well as the distance, which in this case is d = 2460 pc. The spectral types derived from the BCD method and those obtained by Evans et al (2005) using the MK system agree excellently. However, T eff values obtained with the BCD method show in general a good agreement with the values derived by Dufton et al (2006), although some discrepancies of about of 2000 K are observed in subtypes B1 and B2; i.e.…”
Section: Ngc 4755mentioning
confidence: 63%
See 1 more Smart Citation
“…A critical examination by Maeder et al (2014) of the nitrogen abundances estimated in the FLAMES survey (Evans et al 2005;Hunter et al 2008a) advocated the use of N/C against N/O abundance ratio diagrams. In theory, this could provide a powerful diagnostic.…”
Section: Element Abundancesmentioning
confidence: 99%
“…The VLT-FLAMES Survey of massive stars (Evans et al 2005(Evans et al , 2006 provided high-quality observations of an unprecedented number of B-type stars in the Galaxy and the Large and Small Magellanic Clouds (LMC and SMC, respectively). Quantitative analysis of these objects was presented in a series of articles by Dufton et al (2006), Trundle et al (2007), Hunter et al (2007Hunter et al ( , 2008aHunter et al ( ,b, 2009a, and Dunstall et al (2011).…”
Section: Introductionmentioning
confidence: 99%